PWE-149 Thoracoscopic-assisted oesophagectomy for early oesophageal cancer: outcomes for the first 50 resections. (22nd June 2015) - Couper, G; Proctor, M; Lamb, P; MacDonald, A; Paterson-Brown, S; Plevris, J; Penman, I
Abstract : Introduction: Since 2005 it has been unit policy to offer patients staged with T1N0 oesophageal cancer (either unsuitable for endoscopic mucosal resection (EMR) or with features on the EMR specimen that warranted resection) or T2N0 lesions a thoracoscopic-assisted oesophagectomy (TAO). We report on the surgical outcomes and survival for patients treated with this management approach. Method: Results of the first 50 patients with this approach were obtained from a prospectively gathered database. All had staging with endoscopy, computerised tomography (CT) and endoscopic ultrasound (EUS). Depending on EUS assessment, patients were listed for EMR or directly to TAO. TAO was performed using a prone position for thoracoscopic mobilisation. Median follow up was 60 months and was complete for all patients. Survival was calculated using Kaplan-Meier estimates. Results: The median age was 67 years (range 46–81). There were 34 males and 16 females. 48/50 (96%) patients had a TAO. Two patients were converted at an early operative stage to an Ivor Lewis oesophagogastrectomy due to dense pleural adhesions. Stomach was used as a conduit in 49 cases with a colonic interposition in one patient. There were no chyle leaks. There were no significant haemorrhages during thoracic dissection. The median blood loss was 300 mls (range 65–1530). The median number of lymph nodes was 12 (range 4–37). There was one post-operative death. Significant complications included tracheo-oesophageal fistula in 2 patients, 1 tube-tip necrosis, 4 patients with left recurrent laryngeal nerve palsy and 4 anastomotic leaks. Final histology showed HGD in 3 cases, T1a in 18, T1b in 23, T2 in 4 and T3 in 2 patients. There were 9 squamous cell tumours, 38 adenocarcinomas and the 3 patients with HGD. When compared to final histology 48/50 patients (96%) were correctly staged preoperatively as node negative with a combination of CT and EUS. The cancer specific 5-year survival was 95% and overall 5-year survival was 84%. Conclusion: Patients with T1/T2 node negative oesophageal cancer have an excellent prognosis following TAO. This can be achieved with a protocol that must include EUS and access to EMR. It is essential that preoperative staging is accurate to ensure that patients with T1 or T2 lesions who are node positive are offered neoadjuvant therapy. TAO is a safe and effective alternative to open oesophagectomy. Disclosure of interest: None Declared.